Implementation of Accelerated Outcome of Health Service in Yahukimo District Papua Province - Aloisius Giyai; Murtir Jeddawi; Ella l. Wargadinata; Megandaru W. Kawuryan (Yayasan Riset dan Pengembangan Intelektual, 2023)
There are many factors that cause the performance of health services in Papua to be still low compared to other regions, including related to the number of health facilities and personnel, management of health facilities and personnel, geographical conditions, supporting facilities and infrastructure, community awareness, and especially in the field of health services, especially the Yahukimo district. This study uses a qualitative approach with descriptive methods, namely data collection by interviews, documentation and observation with data analysis, namely data reduction (data reduction), data display (display data), and conclusion drawing/verification (drawing conclusions/verification) with triangulation techniques on the data obtained. The implementation of the Acceleration of Health Service Outreach in Yahukimo District, Papua Province has not been fully felt by the OAP community and the results achieved have not been optimal in developing efforts to prevent and eradicate diseases, especially in reducing morbidity, mortality and disability caused by communicable, non-communicable diseases as well as outbreaks and disasters. procedurally this policy is appropriate, but in terms of time, cost, place and implementation because it has not met the standard, quality, equitable and affordable and promotes OAP community participation in the health sector. From the results of the discussion of the Efficiency dimension, it cannot be said to be Efficiency because the Policy has not yet been fulfilled in realizing adequate health services for OAP, because the implementation of health services in health service units and visits to residential housing of OAP has not been carried out optimally as a solution for researchers to make the AGIYAI Model (Ability, Government, Innovation, Yield, Acceleration Of Service Coverage, Implementation). This model is offered and is considered a suitable model for accelerating the reach of health services in Yahukimo District, Papua Province.